Portal hypertension in common variable immunodeficiency disorders – a single center analysis on clinical and immunological parameter in 196 patients - Hanitsch, Leif G.; Steiner, Sophie; Schumann, Michael; Wittke, Kirsten; Kedor, Claudia; Scheibenbogen, Carmen; Fischer, Andreas (Frontiers in Immunology, 2023)
Background: Liver manifestations and in particular portal hypertension contribute significantly to morbidity and mortality of patients with common variable immunodeficiency disorders (CVID). Screening strategies and early detection are limited due to the lack of specific diagnostic tools. Methods: We evaluated clinical, immunological, histological and imaging parameter in CVID patients with clinical manifestation of portal hypertension (CVID+PH). Results: Portal hypertension was present in 5.6% of CVID patients and was associated with high clinical burden and increased mortality (18%). Longitudinal data on clinical and immunological parameter in patients before and during clinically manifest portal hypertension revealed a growing splenomegaly, increasing GGT and sIL-2R levels with decreasing platelets over time. While ultrasound of the liver failed to detect signs of portal hypertension in most affected patients, transient elastography was elevated in all patients. All CVID+PH patients had reduced naïve CD45RA+CD4+ T-cells (mean of 6,2%). Frequency of severe B-lymphocytopenia (Euroclass B-) was higher in CVID+PH patients. The main histological findings included lymphocytic infiltration, nodular regenerative hyperplasia-like changes (NRH-LC) and porto(-septal) fibrosis. Conclusion: CVID patients with lower naïve CD45RA+CD4+ T-cells or severely reduced B-cells might be at higher risk for portal hypertension. The combination of biochemical (increasing sIL-2R, GGT and decreasing platelets) and imaging parameter (increasing splenomegaly) should raise suspicion for beginning portal hypertension.